Characterization of maladaptative perfectionism in late childhood - Chemisquy, Sonia (2019)
Maladaptive perfectionism is the tendency to self-impose unrealistic goals and stringent performance standards, to worry excessively about making mistakes, and to engage in auto-critical self-evaluation. This attribute could negatively impact the psychological well-being of children. The objective of this work was to describe maladaptive perfectionism manifestations in children, and to assess its differences according to sex, school grade, kind of educational institution (public or private), and region of origin. An empiric, descriptive and cross-sectional investigation was made. Participants were 1067 children between 9 and 12 years old, students of public and private schools from two Argentinian provinces (Misiones and Entre Ríos). Results verified the presence of maladaptive perfectionism during early childhood. The most salient manifestation of perfectionism was self-oriented, especially related to school. Socially prescribed and finally other-oriented perfectionism were found next in order of importance. The most vulnerable population profile found was fourth grade children from Misiones’ public schools. These results could be very important to design strategies aimed to treat this mental health problem or to prevent its negative consequences during late childhood.